Effect of different levels of ethanol addition on performance, emission, and combustion characteristics of a gasoline engine - Köten, Hasan; Karagöz, Yasin; Balcı, Özgün (Advances in mechanical engineering, 2020)
In this study, a four-stroke, naturally aspirated, single-cylinder, spark ignition engine was operated with neat gasoline fuel. In-cylinder pressure, performance, and emission values were obtained at full load and 2400-r/min constant engine speed. Using these values, a single-dimensional theoretical model was calibrated. A Kistler spark plug–type pressure sensor was used to obtain in-cylinder pressure. After validation of this single-dimensional theoretical model obtained by the help of a commercial engine analysis software (AVL-Boost), different levels of ethanol addition (2.5%, 5%, 10%, 15%, and 20%) into gasoline were analyzed and compared with neat gasoline fueled conditions. According to obtained results, NO x emissions increased with incremental amount of ethanol. The CO and total hydrocarbons emissions decreased; however, they can be controlled using after-treatment systems such as three-way catalyst.